Leading indicators for Euroland's business cycle - Jörg Döpke (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
The paper investigates a set of possible leading indicators for Euroland's business cycle using aggregated quarterly data. The theoretical plausibility, the behavior at business cycle turning points and the mean leads are analyzed. Furthermore, evidence from cross-correlations and Granger-causality tests is presented. Taking all evidence together, real monetary aggregates, nominal interest rates and the interest rate spread are recommended as leading indicators, whereas survey data on order inflow and production expectations are the best coincident indicators.
Keywords: E32; 330; Business Cycle; Leading Indicator; European Monetary Union; Konjunkturindikator; Konjunkturprognose; Prognoseverfahren; Schätzung; Europäische Wirtschafts- und Währungsunion; EU-Staaten